2021
DOI: 10.1016/j.bioorg.2021.104889
|View full text |Cite
|
Sign up to set email alerts
|

Ebsulfur and Ebselen as highly potent scaffolds for the development of potential SARS-CoV-2 antivirals

Abstract: The emerging COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has raised a global catastrophe. To date, there is no specific antiviral drug available to combat this virus, except the vaccine. In this study, the main protease (M pro ) required for SARS-CoV-2 viral replication was expressed and purified. Thirty-six compounds were tested as inhibitors of SARS-CoV-2 M pro by fluorescence resonance energy transfer (FRET) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…In this sense, the data obtained herein confirm and extend the view that organoselenium molecules are an important class of compounds that should be further studied for their efficacy in inhibiting SARS-CoV-2 proteases. Furthermore, we suggest that ethaselen, ebselen diselenide, ebsulfur, and methylebselenoxide (which can be obtained from synthetic methodologies already described in the literature [106][107][108][109][110][111][112] ) should be tested in vitro as inhibitors of virus replication and its proteases.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the data obtained herein confirm and extend the view that organoselenium molecules are an important class of compounds that should be further studied for their efficacy in inhibiting SARS-CoV-2 proteases. Furthermore, we suggest that ethaselen, ebselen diselenide, ebsulfur, and methylebselenoxide (which can be obtained from synthetic methodologies already described in the literature [106][107][108][109][110][111][112] ) should be tested in vitro as inhibitors of virus replication and its proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Of the aniline-derived diselenides, the highest catalytic efficiency was observed for compound 3b ( Table 1 , entry 4), which was 5 and 2 times more active than the standards ebselen and diphenyl diselenide, respectively. It is worth noting that the diselenide 3b was more effective than ebselen, which is a pre-clinical drug candidate with pronounced biological activities, including, recently, the inhibition of protease M pro from COVID-19 (SARS-CoV-2) virus [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have been recently described as good antioxidants [ 10 , 11 ], also presenting anti-inflammatory [ 12 , 13 ], antibacterial [ 14 ], antiviral [ 15 ], anticancer [ 16 , 17 , 18 , 19 ], anti-Alzheimer’s [ 20 , 21 , 22 , 23 ] and other activities [ 24 , 25 , 26 , 27 , 28 ]. Furthermore, in relation to the current pandemic of COVID-19, there are some interesting studies available that demonstrate the effectiveness of organoselenium compound (Ebselen) as an antiviral molecule, Figure 1 [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weglarz-Tomczak et al reported a series of ebselen-like structures able to inhibit not only M pro , but also the other pivotal protease, a papain-like protease from SARS-CoV-2 with comparable potencies, in the high micromolar range [ 52 ]. Yang et al prepared a series of ebselen and ebsulfur (compound 23 , Figure 2 ) analogues variously functionalized at the nitrogen atom with aryl, alkyl, benzyl and heteroaryl substituent identifying compounds endowed with a better M pro activity when compared to the native lead compound; interestingly, not only ebselen but also 23 proved to covalently bind M pro [ 53 ]. It is worth mentioning that ebselen-like structures are always more potent when compared to their sulfur analogues.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%